Pengaruh Model Problem Based Learning Berbantuan Augmented Reality Terhadap Hasil Belajar Materi Keragaman Budaya Kelas V SDN 106163 T.A. 2025/2026 - Dogom Rizki Siregar; Waliyul Maulana Siregar; Robenhart Tamba; Apiek Gandamana; Husna Parluhutan Tambunan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Problem Based Learning model assisted by Augmented Reality media on student learning outcomes in Pancasila Education subject, specifically on cultural diversity material for fifth-grade elementary school students. The research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The sample consisted of 44 students from class V-B (control group) and class V-C (experimental group) at SDN 106163 Bandar Klippa. Data collection techniques included tests (pretest and posttest) and documentation. The instrument was tested for validity, reliability, difficulty level, and discriminating power. Data analysis used normality test, homogeneity test, independent sample t-test, and N-Gain test. The results showed that the average posttest score of the experimental class was 84.80, higher than the control class at 80.00. The N-Gain score obtained was 0.6224 in the moderate category. The hypothesis test using independent sample t-test obtained a significance value of 0.047 (p < 0.05), indicating that H₀ is rejected and H₁ is accepted. This proves that the application of the Problem Based Learning model assisted by Augmented Reality has a significant effect on student learning outcomes in cultural diversity material in Pancasila Education subject for fifth-grade students at SDN 106163 Bandar Klippa.